A CFD Application For Modeling Submerged Gas Injection In A Peirce?Smith Converter - Jussi Vaamol (The Minerals, Metals and Materials Society, 1998)
A commercial CFD-code was used to solve isothermal flow fields of gas and liquid in a Peirce-Smith converter. The model was validated with a 1/4 scale water model, and parametric study. Limits of the modeling technique used were recognized, but calculated results indicate that the present model predicts the general flow field with reasonable accuracy. The model was used to examine general flow conditions in an industrial scale PS-converter. Typical scaling factors of physical models were also evaluated with the aid of predicted bubble distribution, patterns of the flow fields and magnitude of flow velocities. The numerical simulations were found to open new viewpoints to the fluid dynamic related phenomena in the PS-process.